Pemetaan Marker AFLP untuk Membuat Peta Genetik Bit Gula - Asep Setiawan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2001)
One hundred eighty two AFLP marker using primer combination of EcoRI/MseI and PstI/MseI were used in this study to create a DNA marker genetic map of Sugar beet. In average each primer combination yielded 15.5 polymorphic band AFLP marker using primer combination of EcoRI/MseI significant yielded more polymorphic band than PstI/MseI. From this study a high density DNA marker map coverage all nine chromosomes of sugar beet with totally length of 744 cM Haldane was established. Key words: AFLP, Genetic map, Restriction enzyme, Polymorphic